IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION VALUES AS AN ADAPTIVE STRATEGY TO OVERCOME STUDENT DISCIPLINE VIOLATIONS IN THE CONTEMPORARY ERA - Syafi'i, Iman; Aziz, Yahya; Anas, Ismail; Salamah, Mila Nailis; Afrizatifurrahman Al-Gufron, Muhammad (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2025)
Student disciplinary violations have become a significant educational challenge, particularly in rapid technological advancement and social change. This study aims to identify adaptive strategies that can be implemented to address student disciplinary violations and to analyse relevant challenges and solutions from the perspective of Islamic Religious Education. This research employs a literature review method, a research approach that aims to produce written work based on the analysis of existing literature. The findings indicate that strategies involving restorative approaches, character strengthening based on Islamic values, and the wise use of technology in discipline management are more effective than conventional, repressive methods. Principles in Islamic education, such as spiritual development (tarbiyah ruhiyah), moral cultivation (akhlaq), and exemplary behaviour (uswah hasanah), play a significant role in shaping students' spiritual and moral awareness. The main challenges include the lack of parental involvement, the influence of social media, and limited school resources. Proposed solutions include enhancing collaboration between schools, parents, and communities and using technology to support the development of students' Islamic character. By implementing appropriate adaptive strategies grounded in Islamic values, student disciplinary violations can be minimised, creating a more conducive and harmonious learning environment.